Contribution of All India Investment Institutions (LIC, UTI and GIC) in the Development Finance: Case of India - Pankaj Kumar (Management Journal for Advanced Research, 2023)
The paper examines the performance of All India Investment Institutions contributed to development finance from 1970 to 2022. The secondary data from IDBI Development Bank Report and RBI annual report is retrieved and analysed. Simple descriptive techniques are used in the analysis of assistance sanctioned and disbursed to obtain output. The trends of financial assistance sanctioned and disbursed, growth patterns of assistance sanctioned and disbursed, pattern of sanction-disbursement ratio, and unused funds of investment institutions are analysed. Life Insurance Corporation (LIC), Unit Trust of India (UTI) and General Insurance Corporation (GIC) have played important roles as an all-India investment institution. The result reflects that Unit Trust of India contributed fifty per cent of the total loan contribution followed by LIC till the financial year 2002-03. UTI stopped contribution from 2003-04, then the burden shifted to LIC and GIC. The LIC has been bearing the maximum burden of investment contribution from 2003-04 and has touched a hundred per cent. The GIC never touched the line of UTI and LIC, and since 2017-18 it has stopped investment contributions. Currently, only LIC is contributing to institutional investment for development projects as an All-India Investment Institution. Other investment firms of the government and private sector must take lessons from the successful journey of LIC on one side, and understand the causes of the UTI crisis on the other side.